Practical tips for teaching academic integrity in the digital age - Jenan Younis; Faye Gishen (MedEdPublish, 2019)
Background: Medical education, as with other areas of healthcare education, is susceptible to cheating, with national and international examples cited in the literature. There are documented examples in the lay press, but limited scholarly activity in the field, which can be a challenging area to research and tackle. We have begun to explicitly address academic integrity within our undergraduate curriculum, including a focus on plagiarism, self-plagiarism, and covert sharing of questions. We believe this is an important curricular topic as exhibiting unprofessional behaviours can correlate with professional practice and can potentially have implications for practitioners and patients.